Recombinant DNA studies of the low density lipoprotein receptor gene locus of Afrikaners with familial hypercholesterolemia [Microfiche] - De Waal, Linda(Linda Franziska) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Med. Biochemistry) -- University of Stellenbosch, 1989.